Effect of quantitative easing on ASEAN-5 financial markets - Pathairat Pastpipatkul (2018)
© Springer International Publishing Switzerland 2016. After the economic crisis in 2007, the United States enter to the economic recession. Thus the central banks (Fed) purposed an unconventional policy and launch various programs in order to restore the weak economic. However, it also generated a spillover effects toward Emerging countries through capital flow. Therefore, the paper aims to provide a new empirical finding by examining the effect of quantitative easing (QE) policy of the United States on Thailand, Indonesian, and the Philippine, Singapore, and Malaysian financial markets (ASEAN-5). In this study, the ASEAN-5 financial markets, comprising the exchange rate market, the stock market, and the bond market are considered. To measure the effect of QE on those markets, we employed the Markov-switching VAR model to study the transmission mechanisms of QE shocks between periods of expansion in the QE program and QE tapering. Moreover, we restrict the structure of the model in order to identify the determinant of the structural change. This paper finds that ASEAN-5 financial markets receive the effect form QE. The treasury securities purchase program seems to generate a larger effect to the ASEAN-5 financial market than other programs. Moreover, the test of best MS-VAR specification, provide the result that MSH(2)-VAR(1) is the best specification model for the exchange rate market and the stock market, while MSIH(2)-VAR(1) is the best specification model for bond markets. This indicates that QE was not the factor leading the ASEAN-5 financial markets switch from one regime to another regime.